2023
DOI: 10.1002/smll.202300961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Fluorescent Polymer Micro‐ and Nanoparticles

Abstract: Fluorescent polymer particles have witnessed an increasing interest in recent years, owing to their fascinating physicochemical properties as well as wide‐ranging applications. In this review, the state‐of‐the‐art research progress of fluorescent polymer particles in the past five years is summarized. First, the synthesis protocols for fluorescent polymer particles, including emulsion polymerization, precipitation polymerization, dispersion polymerization, suspension polymerization, nanoprecipitation, self‐ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…On the other hand, using a scratch detector, manufacturers can ensure that their products meet the required quality standards and avoid costly defects and recalls. This phenomenon is very important in aerospace instruments that are under high-pressure exposure . The prepared fluorescent anticounterfeiting powder was utilized for the detection of a generated scratch on the surface of a polycarbonate sheet without using additional reagents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, using a scratch detector, manufacturers can ensure that their products meet the required quality standards and avoid costly defects and recalls. This phenomenon is very important in aerospace instruments that are under high-pressure exposure . The prepared fluorescent anticounterfeiting powder was utilized for the detection of a generated scratch on the surface of a polycarbonate sheet without using additional reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Among the numerous applications of smart inks, their integration with indicators is particularly intriguing. This integration has paved the way for cutting-edge solutions in latent fingerprint identification, scratch detectors, and anticounterfeiting technology. , Dual colorimetric and fluorescent polymer dots were designed by Tsai et al for anticounterfeiting applications . Full-color spiropyran-based photoswitchable polymer dots were prepared through a nanoprecipitation approach and were successfully applied as security inks for pen writing and inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Generally, fluorescent polymeric micromaterials are prepared by labeling the fluorophores, such as organic dyes, quantum dots, and rare earth element materials, on polymers by chemical or physical methods. [ 12 ] However, conventional fluorophores often suffer from low fluorescence efficiencies in aggregate or solid states and poor photobleaching resistance because of the aggregation‐caused quenching (ACQ) effect, [ 13 ] which limits the amount of dye that can serve as signaling components in polymeric micromaterial systems as well as the long‐term tracking performance in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Anticounterfeiting, information encryption, confidential signatures, security codes, optical artworks, and authenticity labels are the most important and advanced applications of photoluminescent nanomaterials. In recent years, the remarkable attention to light-responsive nanomaterials in comparison to other stimuli-responsive nanomaterials such as thermochromic, hydrochromic, and solvatochromic nanomaterials is due to their fast responsivity, high sensitivity, and maximum remote controllability toward induced light irradiation as a powerful authentication tool. Observed alarms or responses include color change (photochromism), excitation and emission (fluorescence), afterglow emission (phosphorescence), switching-off or swathing-on of the emission (PET), and most importantly, the color change of fluorescence emission between more than one state (Förster resonance energy transfer (FRET)). A combination of these characteristics in a single composition can result in the development of a new category of light-responsive nanomaterials that have multimode optical properties and responsivities. Such characteristics are useful for the design and preparation of photoluminescent inks with high security and multimode authentication for use in anticounterfeiting technology and information encryption. A short review of studies reported in recent years that have focused on anticounterfeiting and encryption displays significant challenges for the security level, intensity, durability of optical properties (emission, color, and responsivity), and printability of inks on different substrates. Using photoluminescent nanomaterials is the best solution for the second and third challenges because of the intensity of optical properties, the printability of which increased with the decrease in particle size to below 200 nm.…”
Section: Introductionmentioning
confidence: 99%